Penataan Sistem Pengarsipan pada Kantor Sekretariat DPRD Kabupaten Lampung Utara - Hutagalung, Simon Sumanjoyo; Agata, Fetri Sya; Fadilah, Nur Aini; Lestari, Puji Ayu (Penerbit Goodwood, 2023)
Purpose: Archive management capacity is important for the performance of local government agencies, so adequate human resources are needed. This activity aims to improve the performance of archive managers so as to achieve a more effective and efficient archiving quality. Methodology: This activity is carried out with an active mentoring method involving several students implementing the activity. Participation observation activities are implemented through assistance during routine office activities. Evaluation of activities is carried out qualitatively through observation and quantitatively through pre-test and post-test questionnaires. Results: It is known if there have been changes in behavior and skills in some performance indicators. Likewise, quantitatively it is known if there is a change in all indicators of attitudes and skills of the target group. Limitations: Performance performed only on manual archiving activities, not involving technology or other tool support. Contribution: The results of this study will be useful for archiving activities, lecturers and archival students who need insight into archiving activities at the DPRD Office. As a reference for the program to strengthen the capacity of human resources in the field of archives.